2018
DOI: 10.1051/e3sconf/20187411004
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between variation of greenhouse gases concentrations and humidex

Abstract: The increasing greenhouse gases (GHGs) in the atmosphere contribute to increasing average temperature earth’s surface. This research investigated relationship between variation of GHGs and human thermal comfort based on humidity index (humidex). This study applied humidex, an indices to assess the thermal comfort. The analysis was done by examining the observational data from two different monitoring stations in Serpong and Bogor. The result showed that the average CO2 concentration per month ranged between 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Studies (Lewicki et al, 2010;Duo et al, 2018;Afonso & Pires, 2017)have reported the same results. In winter, from Table 2 and Figure 5, the concentrations of CO and CO2 are in an extremely weak and negative correlation with T and decrease with the increase of T. These are in agreement with discussions of studies (Ocak & Turalioglu, 2008;Lewicki et al, 2010;Ma'rufatin & Kusnoputranto, 2018). But O3 has a weak and positive association with T and increased with an increase in T, meaning that the photochemical reaction of ozone seemed to be important in the formation of O3 during the cold season (Duo et al, 2018).…”
Section: Measurement Of the Concentrations Co O3 Co2 Ch4 And H2s With...supporting
confidence: 91%
“…Studies (Lewicki et al, 2010;Duo et al, 2018;Afonso & Pires, 2017)have reported the same results. In winter, from Table 2 and Figure 5, the concentrations of CO and CO2 are in an extremely weak and negative correlation with T and decrease with the increase of T. These are in agreement with discussions of studies (Ocak & Turalioglu, 2008;Lewicki et al, 2010;Ma'rufatin & Kusnoputranto, 2018). But O3 has a weak and positive association with T and increased with an increase in T, meaning that the photochemical reaction of ozone seemed to be important in the formation of O3 during the cold season (Duo et al, 2018).…”
Section: Measurement Of the Concentrations Co O3 Co2 Ch4 And H2s With...supporting
confidence: 91%